Research with Development Ambitions--Partnering with Non-Researchers - Sullivan, Amy; Harding, Amanda; Rooyen, Andre F. van; Vidal, Alain (2014)
To deliver on a development mandate it is necessary to partner. Partnerships should be based on achieving a common goal, through the partners working on complementary objectives. Partnerships should be based on related objectives, where single organisations will not be able to achieve the goal alone, and where the partnership can lead to more rapid achievement of the goals. Preferably partnership should be objective specific, temporary by nature and dynamic. No one entity can completely address the complexity of real world problems—yet they often propose to do just that. Time and money should be invested in diagnosing pathways to impact, including identifying potential partners with mandates to deliver within those areas of impact. Plan for and invest in the long and enlightening process of engagement with partners, including those who will appear (and disappear) along the way.